THE HIGH GLACIAL (LAST ICE AGE AND LGM) ICE COVER IN HIGH AND CENTRAL ASIA - Kuhle M. (My University, 2004)
This chapter discusses ancient ice-marginal positions that are scattered throughout the high regions of Asia. This represents equilibrium line altitude (ELA) depressions of more than 1000m and indicates, locally, a glacial cover. It discusses that the field investigations to reconstruct the extent of Pleistocene glaciation in the mountains and highlands of central and south Asia have concentrated on identifying former glaciations and their spatial arrangements. This glacial gemorphological approach, on which the digital map is based, has also been discussed in the chapter. The enormous uplift rate of Tibet of approximately 10mm/a measured by triangulations since the 19th century have been confirmed by glacial geomorphological as well as seismological investigations of the uplift of the Himalaya. However, these amounts of uplift far exceed any conceivable primary tectonic uplift of the high plateau based on epirogenetic processes alone. Actually, they are much easier explained if a superimposed glacioisostatic compensation movement of Tibet, about 650m, is taken into account.